AN INTERROGATION OF SPINSTER’S NIGHT AND ITS IMPLICATIONS IN WUKARI LOCAL GOVERNMENT AREA OF TARABA STATE - SAMUEL ALEGWU OMANCHI (International Studies Journal)
This paper examines spinster’s night and its implications in Wukari Local Government Area of Taraba State. It discussesthe implications of spinster’s night in the area. Theorigin and developmentof spinster’s night in Wukarialso came into focus. It analyzes the organization and challengesof spinster’s night in the area. It concludes and made recommendations. The study relied on both primary sources like oral interviews and archival materials and secondary sources like books, theses, articles, newspapers, journals, etc. The study finds out that spinster’s night is part and parcel of most marriagesin Wukari Local Government Area of Taraba State. The study demonstrates that spinster’s night is an important component of Wukari socio-economic sphere as it provides employment to many people in the area and doubled as a veritable tool for social interaction, cross-fertilization of ideas, celebration, and commemoration.In conclusion, the data synthesize from our sources support the claims that spinster’s night, for all intents and purposes, is an important component of Wukari socio-economic sphere.